Mozambique Economic Update, December 2016 : Facing Hard Choices - World Bank (World Bank, Washington, DC, 2016)
This Mozambique economic update brief for 2016 includes a section on recent economic developments and a discussion of Mozambique’s economic outlook, followed by focus section(s) analyzing issues of particular importance.This has been a testing year for Mozambique. An ongoing downturn, brought about by low commodity prices, drought and conflict, was compounded by the fallout from the discovery of hidden debts in April 2016. The level of debt took an explosive path with the addition of the previously undisclosed loans, making Mozambique one of the countries in Africa with the highest debt to GDP ratios. The rate at which the Mozambican currency depreciated outpaced that of most other African commodity exporters, including Nigeria and Angola, where economic pressures have also been acute. Foreign direct investment (FDI), and exports, are projected to fall by 17 and 8 percent respectively in 2016. Clearly, Mozambique’s macroeconomic stability has been shaken-up. The agenda for restoring economic stability and confidence will stretch into 2017 and possibly beyond. Key items on the agenda include setting a medium term framework for restoring fiscal sustainability, anchored in a target for reducing debt and a credible fiscal adjustment program. Enhanced financial sector surveillance and the strengthening of crisis management instruments is also a priority, particularly if further monetary tightening is in the pipeline in the near term. Moreover, the current economic circumstances highlight the need to manage fiscal risks and contingent liabilities better. In this regard, reforms to develop effective oversight over state-owned enterprises and other public entities are urgent, along with reforms to overhaul the framework for managing guarantees.